Lactic acid bacteria in the meat industry: flavor, function, and food safety - Sivamaruthi, Bhagavathi Sundaram; Kesika, Periyanaina; Rafeek, Safreena Barwin Syed; Sivakumar, Kasthuri; Ramasamy, Shanmuga Priya; Chaiaysut, Chaiyavat; Fukngoen, Pranom; Alagarsamy, Karthikeyan (Frontiers in Microbiology, 2025)
Lactic acid bacteria (LAB) play a pivotal role in the food industry, particularly in the fermentation and preservation of meat products. These Gram-positive, non-spore-forming microorganisms contribute significantly to food safety, shelf-life extension, and sensory quality enhancement through the production of various bioactive compounds, including organic acids, bacteriocins, exopolysaccharides, and gamma-aminobutyric acid. Their antimicrobial and probiotic properties are attributed to inhibiting the growth of spoilage organisms and foodborne pathogens, thereby reducing the reliance on synthetic preservatives. This review discusses the general characteristics and selection criteria of LAB, with a focus on their biochemical contributions to the development of flavor, texture, and functional properties in meat-based products. LABs are increasingly being recognized for their potential as natural bio-preservatives, aligning with the growing consumer demand for clean-label and functional foods. However, several challenges persist, including strain-specific variability in functional properties, safety assessments, optimization of metabolite production, and consumer perception. Addressing these limitations through multidisciplinary research and technological innovation is essential to enhance the effective and sustainable application of LAB in the meat industry.